PERANAN TERAPI KEAGAMAAN TERHADAP PASIEN PECANDU NARKOBA DI PANTI REHABILITASI AL KAMAL SIBOLANGIT CENTER - Dahlia Lubis; Faisal Riza; Irohtul Abidah (UIN Sumatera Utara, 2020)
This study aims to determine the role of religious therapy in the rehabilitation process of drug addicts in the al-Kamal rehabilitation center at the Sibolangit Center. The research method used is descriptive qualitative, namely by parsing, explaining, and describing the problems that are closely related to the research. Data collection techniques were carried out by observation, interviews involving counselors, religious counselors and some patietnts and documentation. The data analysis techique in this studi is a qualitative data analysis teachnique using adjusted effectiveness indicators and then analyzed through the stages of data collection, reduction, presentation and data conclusion. This research was conducted at the Al Kamal Sibolangit Center rehabilitation Center. The results obtained show that the role of religious therapy in drug addicts patients carried out at the Al-Kamal rehabilitation center at the Sibolangit Center greatly affects the recovery process for the patient until the time specified by the patient can return to normal witgg a healthy mentel and physical health. The obstacles and constraints faced by patients when carrying out religious therapy are their emotional instability, then various factors from their families, such as a lot of pressure from their families or a lack of love from their families and so on.Keywords: Religious Therapy, Drug Addicts Patients, Rehabilitation Homes.